213k views
2 votes
How do i simplify -5(x+9)=-5

User Marcusshep
by
4.9k points

2 Answers

4 votes

Answer:

-5x+(-45)=-5

-5x=40

x=-8

Explanation:

you multiply everything inside the parenthesis by the -5

then you move the -45 to the other side since the -5 is there

Next you divide by x=-8

User Dawn
by
4.8k points
3 votes

Answer:

Explanation:

-5(x + 9 ) = -5

-5*x + (-5) * 9 = -5

-5x - 45 = -5 {Add 45 to both the sides}

-5x - 45 + 45 = - 5 +45

-5x + 0 = 40

-5x = 40 {Divide both sides by (-5)

-5x/-5 = 40/-5

x = -8

User Rsaesha
by
5.3k points